2012
DOI: 10.1021/jp3032995
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin Readily Switches Conformation upon Protonating High pKaAcidic Residues

Abstract: We investigate protonation as a possible route for triggering conformational change in proteins by focusing on the calmodulin (CaM) example. Two hundred nanosecond molecular dynamics (MD) simulations are performed on both the extended and compact forms of calcium loaded CaM. The stability of both structures is confirmed under prevailing conditions. Protonation of nine acidic residues with upshifted pK(a) values leads to a large conformational change in less than 100 ns. The structure attained is consistent wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 54 publications
1
15
1
Order By: Relevance
“…We note that our perturbation-response scanning method [14,28] can pinpoint such positions, as exemplified here by D52 and another charged surface residue, E31 in our previous work on calmodulin [47]. In contrast to the current work, the latter study demonstrated that large conformational changes related to calmodulin function were induced by the perturbation of the single residue [44], or the protonation of a group of residues mimicking the low pH environment [48].…”
Section: Discussionmentioning
confidence: 52%
“…We note that our perturbation-response scanning method [14,28] can pinpoint such positions, as exemplified here by D52 and another charged surface residue, E31 in our previous work on calmodulin [47]. In contrast to the current work, the latter study demonstrated that large conformational changes related to calmodulin function were induced by the perturbation of the single residue [44], or the protonation of a group of residues mimicking the low pH environment [48].…”
Section: Discussionmentioning
confidence: 52%
“…We do not go into the details of these runs since we have already published a detailed account of the conformations sampled and key events leading to the conformational change [24]. However, it suffices to say that the same sequence of states I→II→III are followed in both runs.…”
Section: Resultsmentioning
confidence: 99%
“…For this we monitor the distance distribution between the residues numbers 34 and 110 throughout the simulation. A normalized cumulative distance distribution is then calculated which shows a trend similar to what is observed in the lower pH case [ 15 , 16 ]. These normalized distance distributions are calculated at the end of the 100 ns simulations of the native structure.…”
Section: Resultsmentioning
confidence: 79%
“…The distance distributions are calculated between the residues 34 and 110, observed at the end of 100 ns as in [ 12 , 15 , 16 ] which gives a measure of the compactness of the protein structure. The respective normalized distance distributions are as seen in Figure 3 with different stages of the calcium ion removal from the protein shown in different colors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation